Application Of Thebranch And Bound In Optimizing The Amount Of Bread Production In CV. Zuhro Bakery Perbaungan - Novita Sari Dewi; James Piter Marbun (Lembaga Pengembangan Kinerja Dosen, 2023)
Zuhro Bakery is baking factory producing various kinds of bread. In this research, there were three kinds of bread that were studied, they were chocolate, mocha and strawberry flavored bread. The problem in optimalization of the production was modeled into a mathematic model which was the linear program in the form obstacle function and objective function. It was then continued by the deciding variable in integer number as the linear program. Then, it was solved by using Branch and Bound method which previously had counted the variable by using the symplex method. From the simplex method, an integer number result was not found, so the Branch and Bound method was used. QM software was chosen in the research to solve the integer problem. A profit was earned with a sale margin of Rp39.000 or 0,42% from the coorporation’s expected profit by using the Branch and Bound method. The amount of bread produced in the periode of three days were 5.400 consosted of 3.060 chocolate flavored bread, 1.440 mocha flavored bread and 900 strawberry flavored bread with the total profit of Rp9.279.000